Na+,-K+-ATPase Deficiency Exacerbates Cardiac Fibrosis via Promoting ERRα-Mediated Myocardial Cell Injury and Macrophage Activation Under Isoproterenol-Challenged Conditions - Ting Lei; Tao Liu; Yutong Liu; Yingnan Zhai; Ruijia Wang; Xiaoyi Tan; Hongli Liu; Xiaofei Yan (Frontiers in Bioscience-Landmark)
Background: Inflammation plays a pivotal role in the progression of tissue fibrosis. Our previous research demonstrated that Na+, K+-ATPase (NKA) α1 deficiency impairs mitochondrial function and accelerates isoproterenol (ISO)-induced cardiac remodeling. This study aims to investigate the interplay between inflammation and NKAα1 deficiency in ISO-induced cardiac fibrosis. Methods: Age-matched male wild-type (WT) and NKAα1+/- mice received daily subcutaneous injections of ISO (30 mg/kg body weight) over 14 consecutive days. Comprehensive histopathological evaluation was performed to assess myocardial architecture and leukocyte infiltration profiles. Mitochondrial ultrastructure was analyzed using transmission electron microscopy. The molecular techniques of real-time quantitative polymerase chain reaction (RT-qPCR), immunoblotting, and enzyme-linked immunosorbent assay (ELISA) were utilized to quantify fibrotic markers and inflammatory mediators. A cell co-culture model was established to investigate the interactions between different cell types. Results: NKAα1 haploinsufficiency exacerbated heart lesions and fibrosis, led to macrophage accumulation, and increased the expression of inflammatory factors in ISO-challenged hearts. Although NKAα1 deficiency did not directly activate macrophages or fibroblasts under ISO conditions, it significantly accelerated cardiomyocyte death in response to ISO insult. Paracrine crosstalk between damaged NKAα1+/- cardiomyocytes, macrophages, and fibroblasts amplified macrophage activation, inflammatory cytokine release, and fibroblast differentiation. Estrogen-related receptor α (ERRα) was identified as a key mediator of NKAα1 haploinsufficiency-induced cardiomyocyte death and interleukin-18 (IL-18) release. Furthermore, treatment with an NKAα1 897DVEDSYGQQWTYEQR911 (DR)-region antibody mitigated ISO-induced cardiac fibrosis and macrophage infiltration. Conclusion: This study provides evidence that NKAα1 deficiency exacerbates cardiac fibrosis by promoting ERRα-dependent cardiomyocyte death and by facilitating intercellular cross-talk between damaged NKAα1+/- cardiomyocytes, macrophages, and fibroblasts. Based on these findings, we suggest that NKAα1 may be a potential regulator of cardiac fibrosis, and that its DR-region represents a potential therapeutic target.